Analysis of Disaster Risk Communication Strategies in the Disaster-Resilient Village Program in Sidomulyo Flower Tourism Village By BPBD Batu City - Salsabila, Laluna; Pia Wulandari, Maulina; Safitri, Reza (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Disaster risk communication is an important thing to convey to the public so that they can recognize the potential and threats of disaster risk in the surrounding area. This research aims to analyze disaster risk communication strategies in the Disaster Resilient Village Program which has been carried out by BPBD Batu City in the Sidomulyo Flower Tourism Village. This research uses a qualitative approach with a case study method to explore the communication strategies implemented to increase awareness and disaster preparedness among the people of Sidomulyo Flower Tourism Village. Data collection was carried out through observation, in-depth interviews, and documentation studies. The results of the study show that the disaster risk communication strategy can be said to be effective because it is accurate and open. However, the BPBD Batu City is unable to reach all levels of society and has not established relationships with conventional media. This has been analyzed using five critical assumptions by Haddow and Haddow (2014), namely Customer Focus, Leadership Commitment, Inclusion of Communication Planning and Operations, Situational Awarness, and Media Partnership.